NONSTEROIDAL ANTI-INFLAMMATORY DRUGS AFFECT THE OCCURRENCE OF BLEEDING FROM THE LOWER GASTROINTESTINAL TRACT (Web of Medicine: Journal of Medicine, Practice and Nursing, 2024)
The problem of bleeding from the upper gastrointestinal tract is currently one of the most pressing in emergency surgery. This is due to the fact that 76% of patients with gastrointestinal bleeding are young and middle-aged people. The proportion of ulcerative gastroduodenal bleeding alone is up to 59-75%, with a predominance of men (59.6%). At the same time, the number of patients with ulcerative bleeding is constantly increasing and is 90-103 per 100,000 adults per year. The aim of the study was to determine the role of nonsteroidal anti-inflammatory drugs in the development of bleeding from the upper gastrointestinal tract.